Longitudinal automated brain volumetry versus expert visual assessment of atrophy progression on MRI: an exploratory study - Gebest, Max Philipp; Weiß, Christel; Cho, Chang Gyu; Hausner, Lucrezia; Frölich, Lutz; Förster, Alex; Santhanam, Nandhini; Fontana, Johann; Groden, Christoph; Wenz, Holger; Maros, Máté E. (Scientific reports, 2025)
Automated tools have been proposed to quantify brain volume for suspected dementia diagnoses. However, their robustness in longitudinal, real-life cohorts remains unexplored. This exploratory study examined if expert visual assessment (EVA) of atrophy progression is reflected by automated volumetric analyses (AVA) on sequential MR-imaging. We analyzed a random subset of 20 patients with two consecutive 3D T1-weighted examinations (median follow-up 4.0 years, LQ-UQ: 2.1-5.2, range: 0.2-10). Thirteen (65%) with cognitive decline, the remaining with other neuropsychiatric diseases. EVA was performed by two blinded neuroradiologists using a 3 or 5-point Likert scale for atrophy progression (scores $$±$$0-2: no, probable and certain progression or decrease, respectively) in dementia-relevant brain regions (frontal-, parietal-, temporal lobes, hippocampi, ventricles). Differences of AVA-volumes were normalized to baseline (delta). Inter-rater agreement of EVA scores was excellent (κ = 0.92). AVA-delta and EVA showed significant global associations for the right hippocampus (pKW = 0.035), left temporal lobe (pKW = 0.0092), ventricle volume (pKW = 0.0091) and a weak association for the parietal lobe (pKW = 0.067). Post hoc testing revealed additional significant link for the left hippocampus (pWSRT = 0.039). In conclusion, the associations between volumetric deltas and EVA of atrophy progression showed promising results for certain brain regions. However, AVA-deltas exhibited unexpected variance, highlighting the need for caution and expert visual confirmation, particularly when scanners or acquisition protocols vary during follow-ups. Therefore, further validation, ideally in large prospective cohorts, is necessary before AVA can be recommended for routine clinical implementation in longitudinal follow-ups.
Gesehen am 10.06.2025